MAKNA TRANSPARANSI DALAM PENGELOLAAN KEUANGAN DAERAH - Agustinus Salle (Universitas Cenderawasih, 2016)
This article explained transparency sets as a public policy to overcome asymmetric information in regional public finance that could lead to low public trust to local governments.. This referred to issues in local governments’ transparency such as defining the transparency, pressures for transparency, resistant behaviors, impacts of low transparency and alternative policies to improve financial transparency in Papua. Key words: transparency, regional finance, special autonomy.